Extracellular Matrix Stiffness and TGFβ2 Regulate YAP/TAZ Activity in Human Trabecular Meshwork Cells - Li, Haiyan; Raghunathan, VijayKrishna; Stamer, W. Daniel; Ganapathy, Preethi S.; Herberg, Samuel (Frontiers in Cell and Developmental Biology, 2022)
Primary open-angle glaucoma progression is associated with increased human trabecular meshwork (HTM) stiffness and elevated transforming growth factor beta 2 (TGFβ2) levels in the aqueous humor. Increased transcriptional activity of Yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ), central players in mechanotransduction, are implicated in glaucomatous HTM cell dysfunction. Yet, the detailed mechanisms underlying YAP/TAZ modulation in HTM cells in response to alterations in extracellular matrix (ECM) stiffness and TGFβ2 levels are not well understood. Using biomimetic ECM hydrogels with tunable stiffness, here we show that increased ECM stiffness elevates YAP/TAZ nuclear localization potentially through modulating focal adhesions and cytoskeletal rearrangement. Furthermore, TGFβ2 increased nuclear YAP/TAZ in both normal and glaucomatous HTM cells, which was prevented by inhibiting extracellular-signal-regulated kinase and Rho-associated kinase signaling pathways. Filamentous (F)-actin depolymerization reversed TGFβ2-induced YAP/TAZ nuclear localization. YAP/TAZ depletion using siRNA or verteporfin decreased focal adhesions, ECM remodeling and cell contractile properties. Similarly, YAP/TAZ inactivation with verteporfin partially blocked TGFβ2-induced hydrogel contraction and stiffening. Collectively, our data provide evidence for a pathologic role of aberrant YAP/TAZ signaling in glaucomatous HTM cell dysfunction, and may help inform strategies for the development of novel multifactorial approaches to prevent progressive ocular hypertension in glaucoma.